2018
DOI: 10.1016/j.vacuum.2017.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Nucleus-acoustic envelope solitons and their modulational instability in a degenerate quantum plasma system

Abstract: The basic features of nucleus-acoustic (NA) envelope bright and dark solitons, which exist in degenerate quantum plasmas, have been theoretically investigated by deriving the nonlinear Schrödinger (NLS) equation. The reductive perturbation method, which is valid for a small but finite amplitude limit, is employed. It is found that the bright envelope solitons are modulationally unstable, whereas the dark ones are stable. It is also observed that the fundamental properties (viz. Modulational instability (MI) gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
81
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 50 publications
(83 citation statements)
references
References 53 publications
(31 reference statements)
2
81
0
Order By: Relevance
“…We have also observed that the amplitude of the DA envelope solitons remains constant but the width of the DA envelope solitons changes with the variation of the various plasma parameters. Our results have a good agreement with the previous work …”
Section: Resultssupporting
confidence: 93%
“…We have also observed that the amplitude of the DA envelope solitons remains constant but the width of the DA envelope solitons changes with the variation of the various plasma parameters. Our results have a good agreement with the previous work …”
Section: Resultssupporting
confidence: 93%
“…The independent variables are stretched as ξ = ǫ(x − v g t) and τ = ǫ 2 t, where ǫ is a small expansion parameter and v g is the group velocity of the IAWs. The dependent variables [13] can be expressed as…”
Section: Model Equationsmentioning
confidence: 99%
“…Now, by substituting Eqs. (8)- (14) into Eqs. (1)-(2), and (7), and collecting the terms containing ǫ, the first order (m = 1 with l = 1) reduced equations can be written as…”
Section: Derivation Of the Nlsementioning
confidence: 99%
“…The stable and unstable parametric regimes of DAWs are organized by the sign of P and Q of Eq. (28) [14,15,16,17,18,19,20]. When P and Q have same sign (i.e., P/Q > 0), the evolution of the DAWs amplitude is modulationally unstable in presence of the external perturbations.…”
Section: Modulational Instability and Rogue Wavesmentioning
confidence: 99%